The Moral Message of How to Make Millions Before Grandma Dies Movie (Semiotic Analysis of Charles Sanders Pierce) - Limbong, M Susanto Syahputra Manaor; Faridah, (Jurnal Cendekia Media Komunikasi Penelitian dan Pengembangan Pendidikan Islam, 2025)
This study aims to analyze the moral message in the film How to Make Millions Before Grandma Dies through Charles Sanders Peirce's semiotic approach, which includes three main elements: signs, objects, and interpretants. The research method used is qualitative with content analysis techniques. Data were collected through documentation techniques, namely by watching the film in-depth, noting key scenes, and identifying relevant semiotic signs. Data analysis was carried out by interpreting the relationship between the film's signs, objects, and interpretants to reveal the meaning of the moral message contained therein. This film conveys a number of important moral messages, especially regarding family values and love that are more meaningful than material wealth. The moral messages raised include: wealth is not everything, genuine care and attention have more value than material gain, sacrifice in the family is a form of priceless affection, and the importance of appreciating time with family before it is too late. In addition, this film also highlights the importance of forgiving and forgetting past mistakes to find inner peace. The character of Amah, who is depicted as a loving figure, teaches that the true legacy is not physical wealth, but memories, love, and values that are passed on to the next generation. The transformation of the grandson's character, who initially only cared about inheritance, into an individual who cares more about emotional relationships, illustrates the journey towards a deeper understanding of the meaning of happiness. Through this analysis, the study shows that the film How to Make Millions Before Grandma Dies offers a reflection on the importance of family relationships, sacrifice, and true love that goes beyond material things. The results of this analysis not only enrich the study of semiotics by explaining the relationship between signs and moral messages in films but also contribute to the understanding of how films can be a medium for conveying moral values ​​that are relevant to people's lives.